2021
DOI: 10.3390/molecules26082195
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Cyclic Ether 2-Butoxytetrahydrofuran from Sea Cucumber Holothuria scabra against Aβ Aggregate Toxicity in Transgenic Caenorhabditis elegans and Potential Chemical Interaction

Abstract: The pathological finding of amyloid-β (Aβ) aggregates is thought to be a leading cause of untreated Alzheimer’s disease (AD). In this study, we isolated 2-butoxytetrahydrofuran (2-BTHF), a small cyclic ether, from Holothuria scabra and demonstrated its therapeutic potential against AD through the attenuation of Aβ aggregation in a transgenic Caenorhabditis elegans model. Our results revealed that amongst the five H. scabra isolated compounds, 2-BTHF was shown to be the most effective in suppressing worm paraly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“… 19 , 20 Additionally, recent study from our group has shown that 2-butoxytetrahydrofuran (2-BTHF), a cyclic ether isolated from H. scabra , can interact with heat shock factor-1 (HSF-1) transcription factor to upregulate the expression of autophagic genes which mediate the clearance of Aβ aggregates through autophagy-lysosomal pathway. 46 Moreover, in addition to 2-BTHF there may be other bioactive substances in the extracts that exert this activity; for instance, diterpene glycosides or holothurins from H. scabra ethyl acetate extracts has been shown to reduce α-synuclein aggregation by activating the degradation process of autophagy-lysosomal pathway. 47 Therefore, it is likely that the bioactive substances included in the H. scabra extracts may exercise synergistic effects in either directly eliminating Aβ aggregates or indirectly reducing Aβ toxicity as demonstrated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Additionally, recent study from our group has shown that 2-butoxytetrahydrofuran (2-BTHF), a cyclic ether isolated from H. scabra , can interact with heat shock factor-1 (HSF-1) transcription factor to upregulate the expression of autophagic genes which mediate the clearance of Aβ aggregates through autophagy-lysosomal pathway. 46 Moreover, in addition to 2-BTHF there may be other bioactive substances in the extracts that exert this activity; for instance, diterpene glycosides or holothurins from H. scabra ethyl acetate extracts has been shown to reduce α-synuclein aggregation by activating the degradation process of autophagy-lysosomal pathway. 47 Therefore, it is likely that the bioactive substances included in the H. scabra extracts may exercise synergistic effects in either directly eliminating Aβ aggregates or indirectly reducing Aβ toxicity as demonstrated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic C. elegans CL4176 expressed Aβ42 in muscle cells is often used in studies of AD as an in vivo model. Therefore, in vivo experiments were performed with CL4176 to evaluate the feasibility of Tol-D inhibiting Aβ deposition in nematodes and the effect of Tol-D on the lifespan of nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…The vicious changes of these signaling pathways and related signaling factors triggered neuroinflammatory reaction, Tau protein phosphorylation β‐ increased secretion of amyloid precursor, which led to the onset of AD (Figure 2). In general, the paralysis test, the fluorescent staining test of Aβ deposition, the ROS test and the chemotaxis test were used to study the AD resistance of the active substances from natural products in C. elegans (Tangrodchanapong et al, 2021). The cyclic ether 2‐butoxytetrahydrofuran extracted and purified from sea cucumbers could delay the paralysis progression in C. elegans and reduce the amount of Aβ‐forming precipitation, which meant that the cyclic ether 2‐butoxytetrahydrofuran had a great effect to resist AD (Tangrodchanapong et al, 2021).…”
Section: Application Of C Elegans Model To Evaluate Nutrition Of Acti...mentioning
confidence: 99%
“…In general, the paralysis test, the fluorescent staining test of Aβ deposition, the ROS test and the chemotaxis test were used to study the AD resistance of the active substances from natural products in C. elegans (Tangrodchanapong et al, 2021). The cyclic ether 2‐butoxytetrahydrofuran extracted and purified from sea cucumbers could delay the paralysis progression in C. elegans and reduce the amount of Aβ‐forming precipitation, which meant that the cyclic ether 2‐butoxytetrahydrofuran had a great effect to resist AD (Tangrodchanapong et al, 2021). Disulfide‐rich cyclic peptides from Clitoria ternatea could regulate AD through decreasing the neurotoxic aggregation of β‐amyloid peptides and the level of ROS in C. elegans (Kalmankar et al, 2021).…”
Section: Application Of C Elegans Model To Evaluate Nutrition Of Acti...mentioning
confidence: 99%
See 1 more Smart Citation